Impact of smartphone addiction on depression and self‐esteem among nursing students - Sayeda Mohamed Mohamed; Mona Hamdy Mostafa (Wiley, 2020)
Abstract Aim To assess the impact of smartphone addiction on depression and self‐esteem among nursing students. Setting Faculty of Nursing. Design Cross‐sectional, survey‐based research design used in this study. Sample: Stratified random sample consists of 320 nursing students. Tools: Four tools used for data collection: personal data sheet, Hamilton rating scale of depression, smartphone addiction scale and Self‐esteem Inventory. Results About 95.8% of nursing students reported smartphone addiction, while 32.5% were pseudonormal of depression. Twenty‐eight percent of them had low self‐esteem. The study also revealed a statistically significant positive correlation between smartphone addiction and levels of depression. There was a statistically significant negative correlation between levels of depression and self‐esteem.